Current Limitations in the Treatment of Parkinson's and Alzheimer's Diseases: State-of-the-Art and Future Perspective of Polymeric Carriers - Tonda-Turo, Chiara; Origlia, Nicola; Mattu, Clara; Accorroni, Alice; Chiono, Valeria (Current Medicinal Chemistry, 2018)
Alzheimer's and Parkinson's diseases are the most common neurodegenerative diseases worldwide and their incidence is increasing due to the aging population. At the moment, the available therapies are not disease modifying and have several limitations, some of which are discussed in this review. One of the main limitations of these treatments is the low concentration that drugs reach in the central nervous system after systemic administration. Indeed, the presence of biological barriers, particularly the blood-brain barrier (BBB), hinders the effective drug delivery to the brain, reducing the potential benefit coming from the administration of the medication. In this review, the mechanisms of transport across the BBB and new methods to improve drug passage across the BBB are discussed. These methods include non-invasive solutions such as intranasal and intravitreal administration, and the use of nanotechnology solutions based on polymeric carriers when the drug is intravenously injected, orally taken for intestine adsorption or delivered through the dermal mucosa. Also, it provides an analysis of more invasive solutions that include intracranially injected hydrogels and implanted devices for local drug delivery. Efforts in finding new therapeutic drugs blocking neurodegenerative disease progression or reverting their course should be coupled with efforts addressed to efficient drug delivery systems. Hence, new pharmacology discoveries together with advancements in nanotechnologies and biomaterials for regenerative medicine are required to effectively counteract neurodegenerative diseases.
Keywords: nanotechnologies